Relationship Between Types of Motivation and Grades in the English for Academic Purpose (EAP) Course Among Unimas' Students - Evalton, Jiob (Universiti Malaysia Sarawak (UNIMAS), 2005)
This study sought to investigate the grades achieved in English for Academic purpose (EAP) course among students of Universiti Malaysia Sarawak (UNIMAS), the types of motivation endorsed by the samples involved in the study and the correlation between participants' type of motivation and grades achieved in the English for Academic Purpose (EAP) course. A seven - point Likert - Scale questionnaire was administered to 190 Unimas' students who had undergone the EAP course. The questionnaire consisted of 8 items of response and two semi - structured questions. Scores were given to each completed questionnaire based on the Likert Scale. Pearson Correlation tool from the Statistical Package for Social Sciences (SPSS) software was used to obtain the correlation value between types of motivation and grades in the EAP course. An additional instrument used in this study was the interview. Two open - ended questions were asked during the interview. The results showed that the respondents achieved various grades in the EAP course. Based on the data analysis, most respondents also achieved good grades in the EAP course. The findings also revealed that there were more participants who endorsed integrative motivation for learning English than participants who endorsed instrumental motivation for learning English. However, no relationship was found between types of motivation investigated in this study and grades in the EAP course among Unimas' students.